Conductometric Studies of the Ion Association of ?-/?-Alanine Bis-Biguanide Cobalt(III) Iodide in Methanol + Water Mixtures at Different Temperatures - MOHONDAS SINGH, N.; DAVID SINGH, TH.; BAG, G.C.; RAJMUHON SINGH, N. (Asian Journal of Chemistry, 2010)
The conductance behaviour of α-alanine bis biguanide cobalt(III) iodide and β-alanine bis biguanide cobalt(III) iodide have been measured in the concentration range (3.00-1.25) ×10-4 eqv.dm-3 in methanol + water mixtures at 10-35 ºC. The limiting equivalent conductances (Λ) and ion association constants (KA) for various compositions have been calculated using Shedlovsky method. The limiting equivalent conductances (Λ0) and ion association constants (KA) for various composition have been calculated using Shedlovsky method. The Walden products were determined. Based on the composition dependence of the Walden products, the influence of the mixed solvent composition on the solvation of ions has been discussed. For both salts, limiting equivalent conductances increase with raise in temperature and also ion association constants increase with increase in the mole fraction of methanol. The thermodynamic parameters viz., change in free energy (ΔGº), enthalpy (ΔHº) and entropy have been calculated from the values of association constants.